First results of the ISIS1 beam test - Velthuis, J; Cussans, D; Goldstein, J; Mandry, S; Stefanov, K; Zhang, Z; Banda, Y; Cheplakov, A; Damerell, C; Devetak, E; Fopma, J; Gao, R; et al. (2009)
The in situ storage image sensor (ISIS) is a monolithic active pixel sensor with memory cells in each pixel. The memory cells are implemented as a CCD register. This and other features of the sensor make the ISIS an excellent device for detectors that will be used at the International linear collider (ILC), an electron-positron accelerator with a proposed centre-of-mass energy of around 500 GeV. The sensor can be made very thin while retaining a high signal-to-noise ratio. The memory cells can be read out between bunch trains at a relatively low clock speed, hence limiting power consumption. The actual signal charge is stored in potential wells and not on capacitors, minimizing the sensitivity to electromagnetic interference. This paper presents the results of the first beam test of the first ISIS prototype. The measurements made include the signal-to-noise ratio, position resolution and efficiency. © 2008 Elsevier B.V. All rights reserved.